CHOICE OF MARITAL PARTNERS: DO PARENTING STYLES AND PEER PRESSURE HAVE ANY ROLE? - OLASUPO, MATHEW O.; AGBENRO, DARE A. F.; OLASUPO, MOBOLAJI G. (Sokoto Educational Review, 2022)
Determining someone to marry could be one of the most important and difficult decisions a person can make in their life. This prompted the study to investigate the predictive role of parenting styles and peer pressure on the choice of marital partners. A sample of 257 (M = 23.55 years, SD = 3.05) National Youth Service Corps (NYSC) members who were selected through purposive sampling technique responded to the Choice of Marital Partners Scale, Parenting Styles Scale and Peer Pressure scale. Results of the hierarchical multiple regression revealed that authoritative parenting style significantly and positively predicted the choice of marital partner. Authoritarian parenting style significantly and positively predicted the choice of marital partner. Permissive parenting style significantly predicted the choice of marital partner. Finally, peer pressure significantly predicted the choice of marital partner and contributed the highest. The study recommended that Psychologists should develop psycho-education programmes tailored toward infusing the three parenting styles together (authoritarian, authoritative and permissive) as well as positive peer relationships in a bid to actualise better marital partners among adolescents and young adults.